Alleviating Knowledge Overload in IT-HR Collaboration in Information Security Management Via Transactive Memory Systems - Wipawayangkool, Kamphol (Journal of Knowledge Management Practice, 2013)
As human factors are increasingly recognized as real culprits of failures in Information Security Management (ISM), the roles of Human Resource Management (HRM) become more salient with ISM. Unlike practitioners, researchers appear reluctant to acknowledge such emergence. Prior literature has not attempted to link ISM with HRM theoretically. ISM literature suggests that both technical and non-technical aspects be simultaneously considered. Similarly, HRM literature recommends that practices such as staffing and training be treated as a bundle. Evidently, both ISM and HRM teams require a pool of specialized knowledge and skills to manage each of their aspects. Moreover, both teams should collaborate in order to improve the ISM performance of the firm. However, the amount of the knowledge may become overloading to both teams. This paper posits that Transactive Memory System (TMS) can support not only knowledge coordination when each team operates independently, but importantly alleviate the knowledge overload when both teams collaborate. Furthermore, this paper proposes that such collaboration via TMS enables an organization to not only manage its ISM more effectively but can ultimately produce sustainable competitive advantage.